Determining the optimal whole-body vibration dose - response relationship for muscle performance - da Silva-Grigoletto, M. E.; de Hoyo, M.; Sañudo, B.; Carrasco, L.; Garcia-Manso, J. M. (The Journal of Strength and Conditioning Research, 2011)
The aim of this investigation was twofold: first, to determine the optimal duration of a single whole-body vibration (WBV) exposure (phase 1) and second to find out the ideal number of sets per intervention to maximize muscle performance (phase 2). All participants were young (age: 19.4 ± 1.6 years), healthy, physically active men. In both studies, a 30-Hz frequency and a 4-mm peak-to-peak displacement were used. In phase 1, subjects (n = 30) underwent 3 sets of different durations (30, 60, and 90 seconds), whereas in phase 2, subjects (n = 27) underwent 3 interventions where the duration remained fixed at 60 seconds, and the number of sets performed (3, 6, or 9) was modified. The recovery time between sets was set at 2 minutes. In all interventions, each set consisted of 1 isometric repetition in a squat position with knees flexed at 100°. Before and after each session, jump height (countermovement jump [CMJ] and squat jump [SJ]) and power output in half squat (90° knee flexion) were assessed. In phase 1, an improvement in jump ability and power output was observed after the 30- and 60-second intervention (p < 0.01), whereas the 90 second intervention, participants just experienced a decrease in SJ and CMJ (p < 0.05). When comparing the different protocols, the greatest response was achieved using 60 seconds (p < 0.05), which was therefore considered as the optimal duration to be used in phase 2. In the second phase, improvements in jump ability and power output were found with 3 and 6 sets (p < 0.05), whereas with 9 sets, participants actually experienced a decrease in these variables. Intergroup comparison showed a greater effect for the program of 6 sets (p < 0.05). In conclusion, a WBV intervention consisting of six 60-second sets produces improved muscle performance measured by SJ, CMJ, and power output.